Interpretation of single progesterone measurement in diagnosis of anovulation and defective luteal phase: observations on analysis of the normal range. Issue 6410 (7th January 1984) - Wathen, N C; Perry, L; Lilford, R J; Chard, T
Abstract : Single serum progesterone determinations were made in 79 apparently normal women with a regular menstrual cycle. A normal range (40 subjects) was derived from the concentrations in the follicular phase and used to define an "anovular" range for luteal phase values (nine out of 39 subjects). The remaining luteal phase values were used to construct an "ovular" range for the luteal phase and, within this range, to define a group of values (less than the 20th centile) which could be described as a "defective luteal phase." The cut off limits between ovular and anovular and between normal and defective luteal phases were respectively two and four times the follicular phase median. It is proposed that the numerical findings of this study may be used as a rule of thumb for defining normality and abnormality from a single serum progesterone determination.